“Made in China 2025 Initiative” and Dual Circulation Economy: Reducing Dependence on U.S. Technology - Putra, Ferdian Ahya Al; Prakoso, Septyanto Galan; Devi, Rahma Sintya (Department of International Relations, Faculty of Social and Political Science, Universitas Airlangga, 2024)
The “Made in China” 2025 Initiative and Dual Circular Economy emerged as strategies to propel China towards becoming a global leader in advanced technologies. It also aims to reduce dependence on foreign technology products, particularly from the United States, since the increased geopolitical tensions and trade disputes arose between the two countries. Meanwhile, the Dual Circulation Economy can be perceived as an economic strategy emphasizing domestic and international circulation of goods, services, and technologies. This strategy prioritizes bolstering domestic innovation, production, and consumption while maintaining selective engagement with the global market. Previous research discussed the topic of Made in China 2025 and Dual Circulation separately. Meanwhile, the study shows close synergy between those strategies in achieving the same goal. This research used a qualitative descriptive method with data collection technique through library research on various sources such as books, journal articles, news, etc. The research used the hegemonic stability theory for analysis. The result reveals that the Dual Circulation Economy provides a framework for nurturing domestic innovation and production capabilities. At the same time, the Made in China 2025 initiative offers a roadmap for advancing industries critical to China's technological independence. This article examines the synergies between these policies and assesses their effectiveness in reducing China's dependence on US technology. It also discusses the implications and the shift in economic strategy to global trade dynamics and geopolitical relations. Keywords: Made in China 2025, Dual Circulation Economy, Technology, China, United States Inisiatif “Made in China” 2025 dan Dual Circular Economy muncul sebagai strategi yang diambil untuk mendorong Tiongkok menjadi pemimpin global dalam teknologi canggih. Inisiatif ini juga bertujuan untuk mengurangi ketergantungan pada produk teknologi asing, khususnya dari Amerika Serikat, mengingat peningkatan ketegangan geopolitik dan sengketa perdagangan antara keduanya. Sementara itu, strategi Dual Circular Economy dapat dianggap sebagai strategi ekonomi yang menekankan sirkulasi barang, jasa, dan teknologi domestik dan internasional, yang memprioritaskan peningkatan inovasi, produksi, dan konsumsi domestik sambil mempertahankan keterlibatan selektif dengan pasar global. Penelitian ini menggunakan metode deskriptif kualitatif dengan teknik pengumpulan data melalui penelitian kepustakaan pada berbagai sumber, menggunakan teori stabilitas hegemonik untuk analisis. Hasil menunjukkan bahwa Dual Circular Economy menyediakan kerangka kerja untuk memelihara inovasi dan kemampuan produksi dalam negeri, sementara inisiatif Made in China 2025 menawarkan peta jalan untuk memajukan industri yang penting bagi kemandirian teknologi China. Artikel ini mengkaji sinergi antara kebijakan-kebijakan ini dan menilai efektivitasnya dalam mengurangi ketergantungan China pada teknologi AS. Artikel ini juga membahas implikasi dan pergeseran strategi ekonomi terhadap dinamika perdagangan global dan hubungan geopolitik. Kata-kata Kunci: Made in China 2025, Dual Circulation Economy, Teknologi, China, Amerika Serikat